2006
DOI: 10.1161/01.res.0000245187.08026.47
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mechanism of Endothelial Nitric Oxide Synthase Activation Mediated by Caveolae Internalization in Endothelial Cells

Abstract: Abstract-Caveolin-1, the caveolae scaffolding protein, binds to and negatively regulates eNOS activity. As caveolin-1 also regulates caveolae-mediated endocytosis after activation of the 60-kDa albumin-binding glycoprotein gp60 in endothelial cells, we addressed the possibility that endothelial NO synthase (eNOS)-dependent NO production was functionally coupled to caveolae internalization. We observed that gp60-induced activation of endocytosis increased NO production within 2 minutes and up to 20 minutes. NOS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
109
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(126 citation statements)
references
References 39 publications
14
109
0
3
Order By: Relevance
“…As such, our in vitro data are consistent with the hypothesis that Thr-495 phosphorylation negatively regulates eNOS activity (13,20,22,44,52,55,56). Previous reports have indicated that phosphorylation of eNOS at Ser-1177 leads to a dissociation of eNOS and caveolin; however, this dissociation was dependent upon the induction of caveolin-dependent endocytosis (57,58). We conclude that phosphorylation of heNOS at Thr-495 plays a role in the regulation of eNOS activity indirectly through the alteration of CaM binding and the association with caveolin.…”
Section: Discussionsupporting
confidence: 91%
“…As such, our in vitro data are consistent with the hypothesis that Thr-495 phosphorylation negatively regulates eNOS activity (13,20,22,44,52,55,56). Previous reports have indicated that phosphorylation of eNOS at Ser-1177 leads to a dissociation of eNOS and caveolin; however, this dissociation was dependent upon the induction of caveolin-dependent endocytosis (57,58). We conclude that phosphorylation of heNOS at Thr-495 plays a role in the regulation of eNOS activity indirectly through the alteration of CaM binding and the association with caveolin.…”
Section: Discussionsupporting
confidence: 91%
“…As the relationship between caveolin-1 and eNOS is dynamic and a prerequisite to homeostasis, it is also plausible that MβCD may reversibly disrupt eNOS localization by altering the membrane organization. These results also support a recent new perspective on the interrelationship between caveolae and eNOS [23] that endothelial dysfunction observed in hypertension is associated with eNOS dysfunction. A tight eNOS-caveolin-1 association attenuates the ability of caveolin to inhibit signaling moieties and enhances cell proliferation [24].…”
Section: Acute Contractile Effect Of Mβcd On Phenylephrine-and High Ksupporting
confidence: 88%
“…Interestingly, we have shown that Src kinase and Akt inhibitors exert additive inhibitory effects on the β 2 -adrenergic relaxant response. Furthermore, Src kinase is known to exert a striking role in eNOS-dependent signaling related to its ability to directly phosphorylate caveolin-1 at Tyr 14 [23] and Src kinase-dependent phosphorylation of caveolin-1 has recently been proposed to promote caveolin-1 dissociation from eNOS, leading to eNOS activation and caveolaemediated endocytosis [31,32]. In this context, we focused on the potential role of caveolin-1 in the additional mechanism responsible for β 2 -AR-dependent eNOS activation.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with -and further supportthis model, as it is the first time, to our knowledge, that the effect of both pharmacological and genetic disruptions was investigated in parallel on a NO-dependent vasorelaxation in a given artery. This point is important because vasorelaxant responses studied in arteries isolated from Cav-1 KO mice have been shown to be decreased, increased or not modified, depending on the vasorelaxant agent or the vascular bed studied [32,[34][35][36]. Regarding the β 2 -AR-mediated vasorelaxation, Neidhold et al reported that it was not modified in the saphenous artery from Cav-1 KO mouse [37].…”
Section: Discussionmentioning
confidence: 99%